2020
DOI: 10.1007/jhep04(2020)116
|View full text |Cite
|
Sign up to set email alerts
|

Natural dark matter and light bosons with an alternative left-right symmetry

Abstract: We perform a consistent analysis of the alternative left-right symmetric model emerging from E 6 grand unification. We include a large set of theoretical and experimental constraints, with a particular emphasis on dark matter observables and collider signals. We show that the exotic neutrino inherent to this class of models, the scotino, is a viable candidate for dark matter satisfying relic density and direct detection constraints. This has strong implications on the scotino mass restricting it to lie in a na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 71 publications
(108 reference statements)
0
20
0
Order By: Relevance
“…To perform our numerical analysis, we have implemented the models presented in section 2 into FeynRules (version 2.3.35) [51] and converted them into leading-order UFO libraries [52,53]. Our new implementations are based on already publicly available ones [18,29,34,54,55], that we have harmonised with each other in the context of simplified versions of the various models (that are sufficient for our purpose). Hard-scattering partonlevel events have then been generated with MG5aMC (version 3.0.3) [56], and have been analysed with MadAnalysis 5 [57][58][59] (version 1.8.58).…”
Section: Computational Setupmentioning
confidence: 99%
“…To perform our numerical analysis, we have implemented the models presented in section 2 into FeynRules (version 2.3.35) [51] and converted them into leading-order UFO libraries [52,53]. Our new implementations are based on already publicly available ones [18,29,34,54,55], that we have harmonised with each other in the context of simplified versions of the various models (that are sufficient for our purpose). Hard-scattering partonlevel events have then been generated with MG5aMC (version 3.0.3) [56], and have been analysed with MadAnalysis 5 [57][58][59] (version 1.8.58).…”
Section: Computational Setupmentioning
confidence: 99%
“…For this, an additional S-symmetry is imposed, under which the lepton number is either L ¼ S − T 3R , in the dark left-right model (DLRM) [29], or L ¼ S þ T 3R , in the dark left-right model 2 (DLRM2) with a global Uð1Þ S [30], duly extended to a local Uð1Þ S in [31]. Finally, it was shown that the partner of the right-handed electron, the scotino, is a viable DM candidate, consistent with all constraints, within suitable parameter space region [26], and the model implications at colliders was explored. In this work, we shall work within the DLRM2, with global S charge assignments as in [27,28,32].…”
Section: The Alternative Left-right Model (Alrm)mentioning
confidence: 58%
“…We have explored the ALRM, an alternate way of extending the SM gauge group with a relatively low energy SUð2Þ R but without any additional symmetry with the left handed sector, either in gauge couplings or in the matter content. As has been shown in earlier studies [21] this opens a way to achieve grand unification within E 6 , while providing a rather unusual model for dark matter and an unusual phenomenology also for the vector bosons at the LHC [26]. Indeed, the scotino [22], the partner of the electron in the right-handed doublet in this model can be a viable dark matter candidate and has been studied in several variants of the model [27,29,30,69].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations